Proteomic Characterization of Proliferation Inhibition of Well-Differentiated Laryngeal Squamous Cell Carcinoma Cells Under Below-Background Radiation in a Deep Underground Environment - Liu, Jifeng; Ma, Tengfei; Gao, Mingzhong; Liu, Yilin; Liu, Jun; Wang, Shichao; Xie, Yike; Wen, Qiao; Wang, Ling; Cheng, Juan; Liu, Shixi; Zou, Jian; et al. (Frontiers in Public Health, 2020)
Background: There has been considerable concern about the potential harmful effects of radiation exposure inducing cancers. However, a few researches focused on the biological effect of below background radiation (BBR) in deep underground environment. To better understand the effect of BBR on cancer, we selected a well-differentiated laryngeal squamous cell carcinoma cell (FD-LSC-1) to observe the biological effect of the BBR in underground laboratory (DUGL). Methods: The growth curve, morphology and quantitative proteomics were performed on the FD-LSC-1 cells cultured in the DUGL and aboveground laboratory (AGL) respectively. Result: Compared with the AGL group, the proliferation of FD-LSC-1 cells of DUGL group was delayed. TEM scan of cells cultured in the DUGL showed that cells had obvious hypertrophic endoplasmic reticulum (ER) and increased number of ER. With a cutoff of∣fold change∣≥1.2 and p value < 0.05, a total of 807 DAPs (536 proteins up-regulated and 271 proteins down-regulated in cells cultured in the DUGL) were detected. KEGG pathway analysis of these DAPs revealed that seven pathways were enriched. These pathways were ribosome (p<0.0001), spliceosome (p=0.0001), oxidative phosphorylation (p=0.0001), Protein export (p=0.0001), Thermogenesis (p=0.0003), protein processing in endoplasmic reticulum (p=0.0108), and Non-alcoholic fatty liver disease (p=0.0421). Conclusion: BBR environment could inhibit proliferation of FD-LSC-1 cells. Additionally, the BBR environment induced the change of protein expression of FD-LSC-1 cells, which covered ribosome, gene spliceosome, RNA transport, energy metabolism etc. These changed proteins might be the molecular basis of the inhibition of proliferation and enhanced survival ability for cells adapting to the BBR in deep underground environment. RPL26, RPS27, ZMAT2, PRPF40A, SNRPD2, SLU7, SRSF5, SRSF3, SNRPF, WFS1, STT3B, CANX, ERP29, HSPA5, COX6B1, UQCRH, ATP6V1G1 were the core proteins in the BBR stress response of cells.